WORKSHOP PENGGUNAAN APLIKASI JOGJA SMART SERVICE SEBAGAI UPAYA MEMPERCEPAT AKSES BANTUAN PADA PERISTIWA BENCANA, KECELAKAAN DAN TINDAK KEKERASAN DI KAMPUNG KEPUH KELURAHAN KLITREN KECAMATAN GONDOKUSUMAN - Erizal, Erizal; Listiawan, Indra (Universitas Respati Yogyakarta, 2021)
Kampung Kepuh is located in a geographic position -7781984, 110184. Kelurahan Klitren has a population of 9669 inhabitants, with a male gender distribution of 4719 people and 4950 women. The area of Kepuh village, which is located in Klitren village, is adjacent to Jalan Solo, which is the second center of shops in Jogjakarta. This condition causes Kepuh village to have the potential for disasters such as fires, prone to traffic accidents and prone to acts of violence such as thieves, pickpockets and robbery. Therefore, it requires easy access to seek assistance for the people of Kepuh village. One access to seeking assistance is the Jogja Smart Service application which can be installed on a cellphone or smartphone. The problem is that the use of cellphones has not been optimal in terms of accessing services for requests for assistance to the city government through the Jogja Smart Service (JSS) application. The solution given was a short workshop with classical and face-to-face methods on the use of the JSS applicationÂ Keywords:Â Disaster-prone, Jogja Smart Service, workshop with a coma